Preliminary Studies on the Oestrogenic Activity of Guinea Grass [Panicum maximum] var. S112 and Stylo [Stylosanthes gracilis] - Adepoju, A.; Adegbola, A. A.; Ayininuola, S. I. (Faculty of Agriculture, University of Ife, 2015)
Purified oestrogenic extracts were obtained from 25g samples of ground air dried leaf and stem portions of guinea grass (Panicum maximum var. S112) and stylo (Stylosanthes gracilis) at four stages of growth. 0.05ml of each of these extracts was injected into immature female mice weighing 8 to 10g in order to determine the oestrogenic activities of the forages at different stages of growth. The mean values obtained for the oestrogenic potency of guinea grass were 0.30, 0.23, 1.41 and 0.86 mcg of diethyl stilbestrol per kg of the leaf portion and 0.28, 0.15, 1.01 and 0.49 mcg of diethyl stilbestrol per kg of the stem portion at early vegetative, full vegetative, early bloom and full bloom growth stages respectively. Mean values for stylo leaf portion were 0.62, 0.85, 1.50 and 0.75 mcg of diethyl stilbestrol per kg, and those for the stem portion were 0.43, 0.62, 0.80 and 0.55 mcg of diethyl stilbestrol per kg at the early vegetative, full vegetative, early bloom and full bloom growth stages, respectively. The results indicated that the oestrogenic content of Stylosanthes gracilis was significantly higher (P .05) than that of guinea grass. for both forages, oestrogen activity was higher (P .05) in the leaf than in the stem, and the differences observed during the various stages of growth were significant.